The bully from the Black Lagoon - Thaler, Mike, 1936- (Black Lagoon, 2008)
Hubie hears about a new kid at school named Butch Pounder, who is supposed to be a bully, and visualizes a variety of horrible rumors, concocting different ways to defend himself.